Implementasi TOPSIS Pada Sistem Rekomendasi Kafe di Kota Malang Berbasis Lokasi - Wiandono Saputro; Ratih Kartika Dewi; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Malang, there are at least 400 cafes and restaurants that college students can visit. A large number of cafes available creates its own problems for college students while looking for a gathering place for refreshing or doing a final assignment, which is choosing which cafe to visit. There are several factors that determine the choice of a cafe such as rating, distance, price, and facilities. To solve this problem, we need a system that can provide cafe recommendations to its users based on the location and the criteria of the cafe they are looking for, also provides information such as prices, menus, coffee beans, brewing methods and directions to the cafe. The cafe recommendation system developed using the TOPSIS. The TOPSIS method is used to generate alternative of cafe based on the concept that the best alternative is not only the the alternative with the shortest distance from the positive ideal solution but also with the farthest distance from the negative ideal solution. Alternative data is stored using the Firebase Realtime Database database service, and directions are given using third-party applications, namely Google Maps. From the testing the system obtained 100% valid on functional testing, 100% valid in the validation of algorithm that compares the system output with manual calculation, and the absence of ranking reversal on rank consistency testing which is done by adding new alternatives, and testing usability based on usefulness, ease of use, ease of learning, and satisfaction which give results in a percentage of 80.55%.